PENERAPAN DATA WAREHOUSE PADA PT. TELKOM YOGYAKARTA (Jurnal Riset Manajemen dan Akuntansi, 2023)
Data warehouse (Warehouse data) is expected to empower mining information to recognize the design in the information, for example when planning procedures that can build agreement and benefit the organization. which method used in Internetsearching research or are called search based strategies online (web), is an information retrieval system through web-based media such as the internet or other network media that provide online facilities. Objective This research is to make it easier for the officers of PT. Telkom Yogyakarta to collect information about accessible products or materials. Result of research the recording and search procedures used by warehouse staff were not effective because it is still being carried out physically, and when the stock taking is carried out, the material is available are often not the same as the results obtained. So with them use a data warehouse system to collect all data carefully and accurate.